Entrepreneurial failure: Statistical and psychological explanations - Artinger, Sabrina; Powell, Thomas C. (Strategic Management Journal, 2016)
Research summary : Entrepreneurial start‐ups suffer high rates of business failure. Previous research on entrepreneurial failure has focused on two kinds of explanations: statistical and psychological. Statistical explanations attribute excess entry to random errors made by boundedly rational entrepreneurs attempting to estimate business opportunities in risky markets. Psychological explanations focus on entrepreneurial overconfidence and competition neglect. These explanations emerged independently and have not been tested or compared in the same study. In this experimental study, we distinguish entrepreneurial markets from other types of markets and test statistical and psychological hypotheses for all market types. We find that excess entry is significantly greater in small, risky markets than in other market types, and that confidence levels account for excess entry, over and above the effects of unbiased statistical errors . Managerial summary : How can we explain the fact that most entrepreneurial ventures fail within five years? Market risk, inadequate capital and inexperienced management certainly play a role. However, from an economic point of view, it seems odd that inexperienced, under‐funded people continue to engage in risky behavior that is widely known to fail. We conducted experiments that tested two explanations of entrepreneurial failure. The first explanation – the statistical hypothesis – argues that entrepreneurship involves high uncertainty, so random errors are inevitable and can produce excess entry (or under‐entry). The second explanation – the psychological hypothesis – says that entrepreneurs' mistakes are not random but skewed heavily toward excess entry; hence, their decisions are distorted by psychological factors such as overconfidence. Our experiments found support for both of these explanations. Random errors under uncertainty explained 60% of the excess entry in our experiments. However, the overconfidence hypothesis correctly predicted that excess entry exceeds under‐entry, and our psychological measures of overconfidence found support in the data. We also found that the markets that most often attract entrepreneurial investment – emerging markets with high uncertainty – were the markets most conducive to excess entry, due to a combination of psychological and market factors. Hence, we conclude that potential entrepreneurs should pay less attention to their own abilities and aspirations, and more attention to the external realities of competition in the marketplace . Copyright © 2015 John Wiley & Sons, Ltd.